Leveraging behavioral science and artificial intelligence to support mental health in the workplace: a pilot study - West, Ashley B.; Guo, Yuzhen Valerie; Bucher, Amy (Frontiers in Psychiatry, 2023)
Introduction: Many American employers seek to alleviate employee mental health symptoms through resources like Employee Assistance Programs (EAPs), yet these programs are often underutilized. This pilot study explores the design of a behavioral science-based email campaign targeting engagement with stress management and mental health resources via an EAP, among employees of a large home builder in the Southeastern US.Methods: Behavioral designers created a behavioral science intervention using a multi-step design approach and evidence based behavioral strategies. For this pilot intervention, employees received either a treatment message (i.e., behavioral science message assembled and delivered via the behavioral reinforcement learning (BRL) agent) or a control message (i.e., a single generic, supportive message with a stock photo) with a call to action to utilize their EAP. This is a provisional file, not the final typeset article Results: A total of 773 employees received emails over the course of one year. Engagement was high, with an 80% email open rate. Over 170 employees (22%, 159 treatment & 14 control) clicked the CTA and logged into the EAP site at least once.